Triple‐band ultra‐thin linear to circular polarization converter based on transmission metasurface. Issue 1 (7th September 2021) - Yuan, Lili; Hou, Lei; Yang, Zhengyi; Zhang, Zheng‐ping
Abstract: In this article, a triple‐band linear‐to‐circular transmissive polarization converter based on metasurface is proposed, which can transform a linearly polarized incident wave into right‐hand circularly polarized wave and left‐hand circularly polarized wave in three nonadjacent frequency bands. Since the proposed polarization converter has a novel structure with only one metallic layer, the proposed converter is ultra‐thin. After simulating, the results demonstrate that the axial ratio of the proposed transmissive circularly converter is below 3‐dB in 7.3–10.4 GHz, 11.9–18.7 GHz and 21.6–29.6 GHz. Additionally, the physical mechanism of multiple resonances is discussed based on equivalent circuit model. Moreover, a prototype is fabricated and measured; the experimental and simulation results are in good agreement. This polarization converter can be employed to manipulate the polarization state of signals in microwave communication.